Selling the CIA : Public Relations and the Culture of Secrecy - McCarthy, David Shamus (Book collections on Project MUSE., 2018)
"In Selling the CIA, David McCarthy contends that events that unfolded during the 1970s badly damaged the CIA's mystique, which had been assiduously cultivated since the Agency's inception in 1947. In response to the unprecedented crisis, CIA officials developed a far-reaching public relations strategy. McCarthy's is the first systematic history of CIA public relations between 1974 and 2014, demonstrating that the culture of secrecy at the CIA and its PR campaigns are fundamentally intertwined"--